Malignant transformation in a fatal case of giant cell tumour of the sacrum. Issue 835 (May 1995) - Crew, J. P.; Flannery, M.; Manners, B.; Coates, C. J.
Abstract : Most giant cell tumours can be treated by local surgery and only rarely are they life threatening. We report a case of a giant cell tumour of the sacrum causing irresectable and fatal small bowel obstruction following malignant transformation of the tumour. The role of radiotherapy in this transformation is discussed.